The Use of Artificial Neural Network for Forecasting of FTSE Bursa Malaysia KLCI Stock Price Index - Ardiansyah, Soleh; Mazlina, Abdul Majid; Jasni, Mohamad Zain (2013)
Stock forecasting has become an issue of interest in financial market. There are many prediction techniques have been reported in stock prediction. Artificial Neural Networks are viewed as one of the more suitable technique for prediction model. In this paper, an experiment on the forecasting of the FTSE Bursa Malaysia Stock Index was conducted to investigate the influence of neural network’s architecture on prediction performance by using multilayer perceptron with Levenberg Marquardt training algorithm. The result show FTSE8 and FTSE9 model achieves closer prediction of the actual value than other models